Activation of RAGE induces elevated O2− generation by mononuclear phagocytes in diabetes - Ding, Yong; Kantarci, Alpdogan; Hasturk, Hatice; Trackman, Philip C.; Malabanan, Alan; Van Dyke, Thomas E. (Journal of leukocyte biology, 2007)
Oxidative stress has been found to play a role in the pathogenesis of diabetic complications. The aim of this study was to define the oxidative burst of diabetic monocytes to characterize the phenotype associated with poor diabetic control. Superoxide (O2−) is the first molecule generated during the respiratory burst of phagocytes by NADPH oxidase, and its generation by monocytes from 26 controls and 34 diabetic subjects was evaluated in this study. Under resting states or stimulation by PMA or opsonized zymosan, diabetic monocytes produce significantly more O2− than nondiabetic cells. The increased O2− generation was found to be correlated with glycemic control (glycated hemoglobin) of patients. To clarify the effects of hyperglycemia on O2− generation, normal human monocytes were treated with receptor for advanced glycation endproducts (RAGE) ligands (AGE protein and S100B) or high glucose media before stimulation. RAGE ligands and high glucose concentration increased O2− generation from human mononuclear phagocytes. RAGE ligands, specifically and potently, increased O2− generation from mononuclear phagocytes, and high‐glucose effects were associated with correspondingly increased osmotic pressure. Differentiated THP‐1 cells, from a human monocytic cell line, were used as a model of human monocytes to study the effects of S100B, the RAGE ligand. It was confirmed that RAGE is involved in the priming of O2− generation by S100B. This study demonstrates that RAGE ligands can contribute significantly to the hyper‐responsive phenotype of diabetic monocytes, which might be reversible by blocking the RAGE or controlling the presence of RAGE ligands by controlling hyperglycemia.